Excitation and properties of large amplitude soliton near foil at laser pulse interaction with it - Maslov, V.I.; Onishchenko, I.N.; Yarovaya, I.P.; Yegorov, A.M. (Вопросы атомной науки и техники, 2012)
The properties and excitation of solitary hump of electric potential of large amplitude, observed in experiment and propagating with thermal velocity of plasma electrons near foil at laser pulse interaction with it, have been described. This soliton has been observed at interaction of laser pulse of duration 1 nsec of power 1014 W/cm2 with foil of thickness 26 μm. The excitation of soliton by nonstationary electrical field has been described for the first time. The properties of soliton has been described in strongly nonlinear case. The dependences of width and velocity of soliton on its amplitude at large values of amplitude have been derived. Both in experiments and numerical simulation it was shown that the width of soliton increases with amplitude growth at large values of amplitude. Описаны свойства и возбуждение наблюдаемого в экспериментах солитонного горба электрического потенциала большой амплитуды, двигающегося с тепловой скоростью электронов плазмы, вблизи фольги при взаимодействии с ней лазерного импульса. Этот солитон наблюдался при взаимодействии с фольгой толщиной 26 микрон, лазерного импульса длительностью 1 нс и мощностью 1014 Вт/см2. Впервые описано возбуждение солитона нестационарным электрическим полем. Описаны свойства солитона в сильно нелинейном случае. Получена зависимость ширины и скорости солитона от его амплитуды при больших ее значениях. Показано, что с ростом амплитуды ширина солитона растет при больших значениях амплитуды, как в экспериментах и численном моделировании. Описані властивості і збудження солітонного горба електричного потенціалу великої амплітуди, який спостерігався в експериментах і рухався з тепловою швидкістю електронів плазми, поблизу фольги при взаємодії з нею лазерного імпульсу. Цей солітон спостерігався при взаємодії з фольгою товщиною 26 мікрон лазерного імпульсу тривалістю 1 нс і потужністю 1014 Вт/см2. Вперше описано збудження солітона нестаціонарним електричним полем. Описані властивості солітона в дуже нелінійному випадку. Отримана залежність ширини та швидкості солітона від його амплітуди при великих її значеннях. Показано, що зі збільшенням амплітуди ширина солітона росте при великих амплітудах, як в експериментах та числовому моделюванні.